Pencegahan Kecenderungan Narsistik Melalui Kontrol Diri - Muliani, Nurintan (Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractSelf-existence can be done by individuals in various ways so that they can be seen by others. This is a natural thing, but is said to be unnatural when it is done excessively so that it can trigger individuals to experience narcissistic tendencies. Narcissistic tendencies are excessive self-love of oneself without regard to others. Individuals who have narcissistic tendencies will experience anxiety, because they will always try to make themselves look unique, special, and perfect in the eyes of the beholder. If this tendency is allowed to become an abnormal or unhealthy personality. Self-control is one way to prevent an individual's narcissistic tendencies from increasing over time. Self-control is an individual's ability to control, structure, and guide behavior in certain situations that will result in positive behavior. Here the author explains that self-control can prevent narcissistic tendencies seen from the existing literature in the form of journals related to narcissistic tendencies and self-control.Â Keywords: Narcissistic, Self-controlÂ AbstrakEksistensi diri dapat dilakukan individu dengan berbagai macam cara agar dapat terlihat orang lain. Ini merupakan hal yang wajar, namun dikatakan tidak wajar ketika dilakukan secara berlebihan sehingga dapat memicu individu mengalami kecenderungan narsistik. Kecenderungan narsistik merupakan self-love yang berlebihan kepada diri sendiri tanpa memperdulikan individu yang lain. Individu yang memiliki kecenderungan narsistik akan merasakan gelisah, karena mereka akan selalu menampilkan usaha untuk membuat diri mereka terlihat unik, istimewa, dan selalu dikagumi di mata orang yang memandang. Jika kecenderungan ini dibiarkan akan menjadi kepribadian abnormal atau tidak sehat. Kontrol diri merupakan salah satu cara agar kecenderungan narsisitik individu tidak meningkat seiring waktu. Kontrol diri adalah kompetensi individu dalam mengontrol, menyusun, dan membimbing perilaku pada situasi tertentu yang akan menghasilkan perilaku yang positif. Berikut penulis memaparkan bahwa kontrol diri dapat mencegah kecenderungan narsistik dilihat dari literatur-literatur yang ada berupa jurnal-jurnal yang berkaitan dengan kecenderungan narsistik dan kontrol diri.